Simplification and Automation of the Administration of Public Relations Services at the Secretariat of the DPRD Sidoarjo Regency: Simplikasi Dan Otomatisasi Tata Laksana Pelayanan Kehumasan di Sekretariat DPRD Kabupaten Sidoarjo - Suwito, Anggara Tri; Mursyidah, Lailul (Universitas Muhammadiyah Sidoarjo, 2021)
Technology is dominating and experiencing rapid development so that public services that are very important for bureaucratic reform are public relations services. Public Relations plays a role in managing information openly and easily accessible to the public so as to realize a transparent, effective, efficient, accountable and accountable state administration. Every Public Agency has the authority to disclose public information, so that the existence of public information disclosure rules for the Sidoarjo Regency DPRD is very important in forming a positive image to the public or society. The method used is descriptive qualitative data obtained through observation, documentation, interviews and using sources from books, journals, and policy documents. The results of this study indicate that the simplification of the automation of management carried out, especially in the field of public relations at the Secretariat of the DPRD Kab. Sidoarjo media facilities Website, Mata Delta application, Instagram and Facebook are still in the process of being repaired and the human resources that manage them are still minimal.